Changes in Cortisol but Not in Brain-Derived Neurotrophic Factor Modulate the Association Between Sleep Disturbances and Major Depression - Santiago, Giuliana Travassos Pires; de Menezes Galvão, Ana Cecília; de Almeida, Raíssa Nóbrega; Mota-Rolim, Sergio Arthuro; Palhano-Fontes, Fernanda; Maia-de-Oliveira, João Paulo; de Araújo, Dráulio Barros; Lobão-Soares, Bruno; Galvão-Coelho, Nicole Leite (Frontiers in Behavioral Neuroscience, 2020)
Sleep disturbance is a symptom consistently found in major depression, which is associated with a longer course of illness, reduced response to treatment and increased risk of relapse and recurrence. Chronic insomnia has been associated with changes in cortisol and serum brain-derived neurotrophic factor (BDNF) levels, which in turn are also changed in major depression. Here we evaluated the relationship between sleep quality, salivary cortisol awakening response (CAR) and BDNF serum levels in patients with sleep disturbance and treatment resistance major depression (n = 18), compared to a control group of healthy subjects with good (n = 21) and poor sleep (n = 18) quality. We observed that the patients had the lowest CAR and sleep duration of all three groups, and a higher latency to sleep than the healthy volunteers with a good sleep profile. Besides, low CAR was correlated with more severe depressive symptoms and worse sleep quality. There was no difference in serum BDNF levels between groups with distinct sleep quality. Taken together, our results showed a relationship between changes in CAR and in sleep quality in patients with treatment-resistant depression, and changes in both were correlated with the severity of depression, suggests that cortisol could be a physiological link between sleep disturbance and major depression.